2022
DOI: 10.2196/33612
|View full text |Cite
|
Sign up to set email alerts
|

Student-Run Online Journal Club Initiative During a Time of Crisis: Survey Study

Abstract: Background Since the closure of university campuses due to COVID-19 in spring 2020 necessitated a quick transition to online courses, medical students were isolated from hospitals and universities, negatively impacting their education. During this time, medical students had no opportunity to participate in academic discussions and were also socially isolated. Furthermore, medical doctors and professors of medical schools were given additional responsibilities during the pandemic because they were t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Case study: Club initiatives Ozkara et al (2022) studied the Cerrahpasa Neuroscience Society Journal Clubs, a group of entirely student-run online journal clubs at Cerrahpasa Faculty of Medicine, Istanbul University-Cerrahpasa, which were founded during spring 2020 during the COVID-19 pandemic in order to enhance medical student education, allow participation in academic discussions, and address social isolation, all of which was affected as the professor were recruited as frontline workers.…”
Section: Graphic T-shirt In the College Spacementioning
confidence: 99%
“…Case study: Club initiatives Ozkara et al (2022) studied the Cerrahpasa Neuroscience Society Journal Clubs, a group of entirely student-run online journal clubs at Cerrahpasa Faculty of Medicine, Istanbul University-Cerrahpasa, which were founded during spring 2020 during the COVID-19 pandemic in order to enhance medical student education, allow participation in academic discussions, and address social isolation, all of which was affected as the professor were recruited as frontline workers.…”
Section: Graphic T-shirt In the College Spacementioning
confidence: 99%
“…The number of attendees varied depending on perhaps both the speaker and topics presented, with different speakers and topics drawing different audience sizes, and thus, the delivery of live and recorded invitations to the surveys varied. To increase future participation in surveys, issuing a journal club participation certificate could be considered, as it resulted in a 100% response rate by a recent student-run, web-based journal club initiative in Turkey [15].…”
Section: Limitationsmentioning
confidence: 99%
“…9,10 Across other teaching institutions, students have entertained the possibility of conducting student-run online journal clubs, with students serving as moderators or academic mentors. 13 Belfi et al and Mark et al showed that a student-centered approach effectively achieved the goal of actively engaging learners to participate in discussions to help hone critical thinking skills and stimulate an engaging platform for discussion. 9,10 Due to the success of TJCs, various medical education institutions have attempted to implement TJC iterations, enabling more active participation among students to better achieve learning outcomes.…”
Section: Interactive Journal Clubsmentioning
confidence: 99%